Development of fibrous balloon for facilitating the use of calcium phosphate cement in vertebral augmentation procedures. (15th November 2018) - Padalhin, Andrew R.; Kim, Boram; Ventura, Reiza D.; Lee, Hyun Jung; Lee, Seung Jin; Lee, Byong-Taek
Abstract: Bone loss and fractures are becoming a common problem due to the aging of the global population. To aid such cases, less invasive procedures for bone regeneration have been developed using injectable bone substitutes. However, injectable materials for bone are commonly composed of inert materials that only provide structural support and still pose a risk of leakage, which contributes to morbidity. This study attempts to address this problem through evaluation of different types of electrospun fibers and their potential for facilitating the use of calcium phosphate-based cement in vertebral augmentation procedure. Thin (0.83 ± 0.31 μm fiber diameter) and thick (5.25 ± 1.22 μm fiber diameter) electrospun polycaprolactone (PCL) membranes were fabricated and surface modified through hydrolysis and simulated body fluid (SBF) apatite deposition. Samples composed of thin fibers generally retain most of their relevant properties following surface modification, while a significant change was observed in samples composed of thick fibers. The results show that thin electrospun fibers possess desirable mechanical properties for injectable cement encapsulation, while thick electrospun fibers provide a better substrate for pre-osteoblast cells. Balloon samples fabricated from both fiber types were used to test inflation capacity, encapsulation of injectable cement, and bone tissue development in an animal model. Graphical abstract: Highlights: Electrospun fibers can be used for encapsulating calcium-phosphate based injectable cement. Fiber diameter, porosity and shape design influences biocompatibility and encapsulation capacity of the fibrous balloon. Thin and thick electrospun fibers can be combined to create an effective encapsulation balloon for injectable CPC cement.